Reflection of Discourse Assignments in the Configuration of Yorùbá Personal Names - Ògúnwálé, Joshua Abíódún (Mediterranean Journal of Social Sciences, 2012)
Using the Speech Act Theory as propounded by Austin (1962) and articulated in Searle (1969), Cole(1975), Traugott and Pratt(1980:229), among others, the paper expatiates on how the speech actconfigurations are instantiated through the Yoruba name words. The configured Yoruba name- texts usedas data for the study are made possible through the nature of lexical complexity and loaded sociosemanticcapacities inherent in the name-words. The objective of the study, therefore, is with a view tocasting an in-dept look at what pragmatic roles the Yoruba names could perform, apart from their merebanal usage as tags for identifying the individuals. The article primarily outlines the general characteristicsof speech acts in discourse and also discusses the structural contents of Yoruba names in order todetermine the extent of their participation in the various name words in the language discourse. Theprimary sources were the names collected from the Voters Registration Cards obtained from theIndependent National Electoral Commission (INEC) Offices in the South- western geo-political zone ofNigeria, where speakers of the Yoruba language originated. The data was supplemented by theintrospection of the author as a native speaker of the language, oral interviews and library sources. Thestudy found that the characterisation of speech acts could be gleaned from the socio-cultural foundationswhich underlie the fabrication of the name-words as they license gratitude, questioning ,solitude,condolence ,apology, reports, denial, summon, declaration, etc. in their pragmatic imports .It is thereforeconcluded that the Yoruba Personal Names(YPNs) can be pragmatically differentiated from the personalnames in the western cultural contexts on the bases that YPNs posses packaged-information which makethem able to perform hosts of discourse roles in communication ,apart from their being a template ofsentence and an encyclopaedia where one can glean the Yoruba view-points on ethical values ,beliefs andhistory, cultural identities, genealogy ,fauna and floral.